Martin Chuzzlewit [videorecording (DVD)] - James, Pedr; Scofield, Paul, 1922-2008; Mills, John, 1908-2005; Postlethwaite, Pete; Wilkinson, Tom, 1948-; Dickens, Charles, 1812-1870 (Warner Home Video, 2005)
Who will inherit the riches of wealthy old Martin Chuzzlewit? The only person he trusts is his companion and nurse, the young orphan Mary Graham, but she is employed on the understanding that she will not inherit a penny. He has disinherited his grandson, Young Martin, suspicious of the motives of the young man's love for Mary. With such a fortune at stake, the rest of the family closes in like sharks. The obsequious Pecksniff, whit his daughters, Mercy and Charity, attempts to grovel into the old man's good graces, while the wicked Jonas will stop at nothing ... even murder.